# Simplify (b + 1)3 - (b - 1)

## Answers

[tex]▪▪▪▪▪▪▪▪▪▪▪▪▪ {\huge\mathfrak{Answer}}▪▪▪▪▪▪▪▪▪▪▪▪▪▪[/tex]

Let's solve :

[tex](b + 1)3 - (b - 1)[/tex][tex]3b + 3 - b + 1[/tex][tex]2b + 4[/tex][tex]4 \frac{4}{7}-3 \frac{5}{7}= \frac{32}{7}- \frac{26}{7}= \frac{6}{7}[/tex]

Its 11w9+10w+5

Step-by-step explanation:

(3 * 10^-6)(6 * 10^-8) =

= (3 * 6) * (10^-6 * 10^-8)

= 18 * 10^-14

= 1.8 * 10^1 * 10^-14

= 1.8 * 10^-13

1. Find the sum 5/2 + (-2/3)

[(5/2)(3/3)] + [(-2/3)(2/3)]

15/6 – 4/6 = 11/6

a. 11/6

2. Which property is illustrated by the statement (4+6.1)+7=4+(6.1+7)

a associative property of addition

3. To which set of real numbers does the number 1/5 belong

b rational numbers

4. What is the algebraic expression for the following word phrase: the product of 2 and y

a 2y

5. What is the simplified form of the expression 1/196

*no correct answer among the choices. 1/196 is the simplified form.

6. Evaluate x/y for x=2/3 and y=6/7

2/3 ÷ 6/7 =>>> 2/3 * 7/6 = 14/18 simplified to 7/9

a 7/9

7. Simplify the expression (3/5)^2

d 9/25

9 which is a solution of the equation y=2x+5

c (3,11)

10. Solve the equation For 4y-2=26

4y = 26 +2 => 4y = 28 => y = 28/4 => y = 7

a 7

answer:

d

step-by-step explanation:

20/12

Scientific notation:

[tex]m\cdot10^{n}[/tex] where [tex]1\leq m < 10\ \wedge\ n\in\mathbb{Z}[/tex]

[tex](3\cdot10^{-6})(6\cdot10^{-8})=(3\cdot6)(10^{-6}\cdot10^{-8})=18\cdot10^{-6+(-8)}\\\\=18\cdot10^{-14}=\dfrac{18\cdot10^{-14}\cdot10}{10}=\dfrac{18}{10}\cdot10^{-14+1}=1.8\cdot10^{-13}[/tex]

C.1.8 x 10^-13

Used:

Commutative Laws [tex]a+b=b+a[/tex]

[tex]a^n\cdot a^m=a^{n+m}[/tex]

Simplify the expression.

7.5(–5.9)

–11.21

14.25

–44.25

44.25

Is this multiple problems..?